Self-efficacy and Motor Skills Acquisition: Systematic Literature Review in - Weilemann Belo, Luísa de Carvalho Cammarota (2024)
Objective. The goal of this paper was to provide a comprehensive overview of the literature focusing on the influence of self-efficacy on performance and learning of motor skills in adults. Method. A systematic literature review examining studies indexed in PubMed, Cochrane, Scielo, PsycArticles, and Pepsic databases was conducted. The following characteristics were extracted from the selected articles: authors and year of publication, publication journal, hypothesis (predictor and criterion variables), sample characteristics, and risk of bias using the PEDro scale. Results. Analysis of the sixteen studies reveals a positive association between self-efficacy and motor performance, and in some studies, with learning. Strategies used to influence self-efficacy varied considerably among studies. There is no consensus on the best approach to influence the interpretation of this construct in adult motor skills training.